Common tumor at a rare site - Murugesan, Anuradha; Prabhu, Karthiga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Extrauterine leiomyomas are rare and are a great diagnostic challenge. Leiomyoma and fibroma are the most common mesenchymal tumours of the vagina. 51-year-old multiparous lady presented with vulvovaginal swelling. On examination, a lobulated firm vulvovaginal mass measuring 6×7 cm, occupying the right posterolateral part of labia majora extending into the lateral vaginal wall was seen. Histopathology was suggestive of Leiomyoma. Leiomyoma should be considered as one of the differential diagnosis of solid vaginal mass.